Climatic Characteristics and Determination Method for Freezing Rain in China - Yue Zhou; Yanyu Yue; Zhengxu Gao; Yuehua Zhou (Advances in Meteorology)
The climatic characteristics and temperature profiles of freezing rain in China are analyzed based on the observational data at 650 stations in China from 2000 to 2015. The freezing rain of China is generally in stripe-shape spatial distribution. The stations with freezing rain over 100 station-hours are mainly concentrated at the southeast areas of Southwest China and high-elevation mountainous areas of Eastern China. There are mainly two types of freezing rain temperature profiles, including single-warm-layer profile and double-warm-layer profile. The freezing rain profiles of mountainous area and urban area in Southwest China are similar to each other, and the freezing rain in Central and East China shares the similar single-warm-layer profile. The profiles in South China show the characteristics of freezing rain’s profile in both Southwest China and Central/East China as the position of stations. PA of freezing rain’s profiles is negatively correlated with NA, with correlation coefficients ranging from −0.36 to −0.70. The configuration of weak cold/warm layer (both smaller than 150°C·hPa) is one of major reasons causing frequent freezing rain at mountainous areas of Southwest China. The more obvious the change of NA with the variations of PA is, the more the freezing rain is likely to occur.